Invasion of fall armyworm, (Spodoptera frugiperda, J E Smith) (Lepidoptera, Noctuidae) on onion in the maize–onion crop sequence from Maharashtra, India - Soumia, P. S.; Shirsat, Dhananjay V.; Chitra, N.; Guru-Pirasanna-Pandi, Govindharaj; Karuppaiah, Vadivelu; Gadge, Ankush S.; Thangasamy, Arunachalam; Mahajan, Vijay (Frontiers in Ecology and Evolution, 2023)
Climate change affects geographical distribution of insect pests which poses threats to the environment, as well as agricultural productivity and production worldwide. Spodoptera frugiperda is commonly known as fall armyworm (FAW), a potential insect pest of monocot crops like maize, wheat, rice and sorghum globally. Among these, maize is the most preferred host crop while worldwide there are very few reports on onion being a host of fall armyworm.The Fall Armyworm (FAW) was identified by examining the morphological characteristics of its immature and mature stages, as well as by analyzing the mitochondrial cytochrome oxidase 1 (COX1) gene. Further, the strain identity was confirmed through multiple sequence alignment with previously identified S. frugiperda strains from corn and rice. Also studied the biology and damage symptoms caused by FAW in onion crops. During our experiments, the incidence of FAW ranged from 5 to 20 percent in different plots. The highest incidence was observed in young crops (30-45 days after transplanting) that were sown in November 2020. The FAW larvae exhibited six instars, with a total larval duration of 22.2 ± 0.37 days. The pest had multiple generations per year. The fully developed larvae formed earthen cocoons in the soil for pupation, with a pupal duration of 8.0 ± 0.45 days. The male adults had a recorded longevity of 6.4± 0.40days, while the female adults lived for approximately 9.2 ± 0.37 days. The COX1 gene sequencing revealed its 100% similarity with Spodoptera frugiperda and the comparison of sequences among FAW infecting rice and maize by using multiple sequence alignment showed differences at 11 positions. The present study is the first report of FAW invasion in onion in India and provides basic ideas about FAW characteristics which will help to control this new invasive pest in onion. In tropical regions with multiple cropping system and seasons, it becomes very important to investigate invasive pests as well as its host range in order to forecast its potential damage and devise suitable control measures.